2018
DOI: 10.1002/jcla.22397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin D receptor gene polymorphisms (Fok‐I and Bsm‐I) in T1DM Saudi children

Abstract: This study emphasizes a positive association between SNPs (Fok-I and Bsm-I) and T1DM among Saudi children with increased risk with the Fok-I F and Bsm-I b alleles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The pathogenetic role of vitamin D in T1DM onset is debated. The Type 1 Diabetes Genetic Consortium, which genotypically characterized 38 single nucleotide polymorphisms (SNPs) in more than 1500 families with T1DM, did not observe correlations between SNPs in the VDR and T1DM [138], even if associations between some VDR polymorphisms (BsmI, FokI, TaqI, ApaI) and T1DM have been pinpointed in several population studies [139][140][141][142][143][144][145][146][147][148]. In 2017, Sahin OA et al [149] published a meta-analysis, with the aim to evaluate the relationship between ApaI, BsmI, FokI, and TaqI polymorphisms of VDR and T1DM in children.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The pathogenetic role of vitamin D in T1DM onset is debated. The Type 1 Diabetes Genetic Consortium, which genotypically characterized 38 single nucleotide polymorphisms (SNPs) in more than 1500 families with T1DM, did not observe correlations between SNPs in the VDR and T1DM [138], even if associations between some VDR polymorphisms (BsmI, FokI, TaqI, ApaI) and T1DM have been pinpointed in several population studies [139][140][141][142][143][144][145][146][147][148]. In 2017, Sahin OA et al [149] published a meta-analysis, with the aim to evaluate the relationship between ApaI, BsmI, FokI, and TaqI polymorphisms of VDR and T1DM in children.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) in the metabolic pathway of VD contribute as the genetic component to VD status. There is a set of studies dedicated to the associations between T1D and mutations related to VD metabolism genes such as VD-binding protein (VDBP), VDR [34,40,41], and CYP24A1. Moreover, polymorphisms in CYP2R1 gene encoding the enzyme involved in 25-hydroxylation of VD were also shown to be associated with a higher risk of T1D.…”
Section: Vitamin D Deficiency and Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Overall, 29 case-control studies with cases and 5578 controls were analyzed for assessment of FokI polymorphism and T1DM risk. Of 29 studies, 15 studies were conducted in European countries [15,[34][35][36][37][38][39][40][41][42][43][44], 9 studies were in Asian countries [45][46][47][48][49][50][51][52][53], 3 studies were in African population [54][55][56] and eventually one study in Australia [57] and one study in American population [58]. Among studies were performed in Europe, Audi et al [37] conducted an association study in different city of Spain (Barcelona and Navarra) and reported all data separately including genotype and allele frequency; thus we considered each population as a separate study.…”
Section: Meta-analysis Of the Association Between Foki (Rs2228570) Pomentioning
confidence: 99%
“…It was detected that 15 studies with 1938 cases and 4450 controls were performed in European countries [15, 34-38, 40-42, 44, 59, 60] which among these 15 studies, Turpeinen et al [36] conducted an association study in different city of Finland (Turku, Tampere and Oulu) and reported all data separately, including genotype and allele frequency; thus we considered each population as a separate study. Moreover, 14 studies out of 35 eligible studies were carried out in Asian populations [46,48,49,52,53,[61][62][63][64][65][68][69][70][71], 3 studies were in Americans [58,67,72] and three studies were in Africans [54,56,66] Table 3.…”
Section: Meta-analysis Of the Association Between Bsmi (Rs1544410) Pomentioning
confidence: 99%